Assessment of root-specific promoters in banana and tobacco and identification of a banana TIP2 promoter with strong root activity - James, Anthony; Paul, Jean-Yves; Souvan, Jacqueline; Cooper, Tal; Dale, James; Harding, Rob; Deo, Pradeep (Frontiers in Plant Science, 2022)
Genetic modification is one possible strategy to generate bananas (Musa spp.) with resistance to the soil-borne pathogen causing Fusarium wilt. The availability of banana root-specific promoters to target transgene expression to the sites of infection would be beneficial. We have assessed 18 promoter sequences derived from a range of plant species for their expression profiles in banana tissues to identify those with root-specific activity. Promoter sequences were isolated and fused to the β-glucuronidase (GUS) gene to assess their expression levels and tissue specificity in both banana and the model plant tobacco. Two heterologous promoters conferring high root expression levels in banana were identified, including a β‐glucosidase 1 (GLU1) promoter from maize and the RB7-type tonoplast intrinsic protein (TIP)-2 promoter from strawberry. Further, a novel Musa TIP2-2 promoter sequence was isolated and characterized which, when fused to the GUS gene, conferred very high GUS expression levels in banana roots. These promoters will expand the options for the control of gene expression in genetically modified bananas, providing a tool to develop plants with resistance not only to soil-borne diseases such as Fusarium wilt, but also for the improvement of other traits, such as nematode resistance, nutrition or abiotic stress resistance.